A village without Solidarity : Polish peasants in years of crisis - Hann, C. M., 1953- (New Haven : Yale University Press, 1985)
This historical and anthropological study of a single rural village in southern Poland presents important insights into the nature of Polish socialism and society at grassroots level.
Includes bibliographical references (pages 203-204) and index.
JSTOR
Keywords: Wisłok Wielki (Poland) -- Social conditions; Wisłok Wielki (Poland) -- Ethnic relations; Ukrainians -- Poland -- Wisłok Wielki; Poland -- Rural conditions -- Case studies; Villages -- Poland -- Case studies; Ukrainiens -- Pologne -- Wistok; Villages -- Pologne -- Cas, Études de; Wistok (Pologne) -- Conditions sociales; Wistok (Pologne) -- Relations interethniques; Pologne -- Conditions rurales -- Cas, Études de; Villages -- Pologne -- Études de cas; POLITICAL SCIENCE -- General; Ethnic relations; Rural conditions; Social conditions; Ukrainians; Villages; Poland; Poland -- Wisłok Wielki; Bauer; Soziale Situation; Wisłok; Fallstudiensammlung; Platteland; Oekraïeners.; Poland -- Rural regions -- Social conditions; boeren; farmers; polen; plattelandsgemeenschappen; rural communities; sociaal milieu; social environment; sociaal welzijn; social welfare; sociologie; sociology; sociale problemen; social problems; sociale situatie; social situation; sociografie; sociography; welzijn; well-being; Rural Society; Rurale samenleving; Fallstudiensammlung; Case studies; Case studies; Études de cas